1996
DOI: 10.1021/ic9604167
|View full text |Cite
|
Sign up to set email alerts
|

SynAnti Isomerism in a Mixed-Ligand Oxorhenium Complex, ReO[SN(R)S][S]

Abstract: The simultaneous action of the tridentate ligand (C(2)H(5))(2)NCH(2)CH(2)N(CH(2)CH(2)SH)(2) and the monodentate coligand HSC(6)H(4)OCH(3) on a suitable ReO(3+) precursor results in a mixture of syn- and anti-oxorhenium complexes, ReO[(C(2)H(5))(2)NCH(2)CH(2)N(CH(2)CH(2)S)(2)] [SC(6)H(4)OCH(3)], in a ratio of 25/1. The complexes are prepared by a ligand exchange reaction using ReO(eg)(2) (eg = ethylene glycol), ReOCl(3)(PPh(3))(2), or Re(V)-citrate as precursor. Both complexes have been characterized by element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 24 publications
6
51
0
Order By: Relevance
“…The major product was eluted at 18 minutes and the minor one at 22 minutes. These retention times were the same as those of the oxorhenium complexes [ReO(L n )(L) 3 ] (1, 2) and [ReO(L n )(L) 2 ] (3,4) suggesting the formation of analogous oxotechnetium complexes, [ 99g TcO(L n )(L) 3 ] (5, 6) and [ 99g TcO(L n )(L) 2 ] (7,8). Three days later, HPLC analysis showed that the peak at 22 minutes became the predominant peak ( Figure 2 trace B) indicating a quantitative transformation of complexes 5 and 6 ([ 99g TcO(L n )(L) 3 ]) to 7 and 8 ([ 99g TcO(L n )(L) 2 ]) respectively.…”
Section: Synthesismentioning
confidence: 56%
See 4 more Smart Citations
“…The major product was eluted at 18 minutes and the minor one at 22 minutes. These retention times were the same as those of the oxorhenium complexes [ReO(L n )(L) 3 ] (1, 2) and [ReO(L n )(L) 2 ] (3,4) suggesting the formation of analogous oxotechnetium complexes, [ 99g TcO(L n )(L) 3 ] (5, 6) and [ 99g TcO(L n )(L) 2 ] (7,8). Three days later, HPLC analysis showed that the peak at 22 minutes became the predominant peak ( Figure 2 trace B) indicating a quantitative transformation of complexes 5 and 6 ([ 99g TcO(L n )(L) 3 ]) to 7 and 8 ([ 99g TcO(L n )(L) 2 ]) respectively.…”
Section: Synthesismentioning
confidence: 56%
“…Meanwhile, in each case, a crystalline product precipitated with an HPLC retention time of 22 minutes (Figure 2 trace C). Elemental analysis, X-ray crystallography, and spectroscopic methods confirm that the crystalline complexes were [ 99g TcO{(CH 3 CH 2 ) 2 NCH 2 CH 2 S}-(SC 6 H 4 OCH 3 ) 2 ] (7) in the case of the L 1 H and [ 99g TcO(C 5 H 10 NCH 2 CH 2 S)(SC 6 H 4 OCH 3 ) 2 ] (8) in the case of the L 2 H ligand. We are once again led to the conclusion that the [ 99g TcO(L n )(L) 3 ] complexes gradually convert to the [ 99g TcO(L n )(L) 2 ] complexes.…”
Section: Synthesismentioning
confidence: 87%
See 3 more Smart Citations